Rubber-Clay Nanocomposites : Science, Technology, and Applications - Galimberti, Maurizio; Wiley InterScience (Online service) (Hoboken, N.J. : John Wiley & Sons, 2011)
"This book comprehensively reviews rubber-clay nanocomposites in a handbook format for R & D professionals. Along with valuable details on synthesis, processing, and mechanics, the book includes applications of rubber-clay nanocomposites in automotive tires and as polymer fillers. In addition, it helps scientists understand processing methods for nanocomposites preparation and nanostructure characterization. This book helps promote common knowledge and interpretation of the important aspects of rubber-clay nanocomposites, clarifying the main results achieved in the field of rubbers and crosslinked rubbers - not covered by the more general books on polymer-clay nanocomposites"--
Frontmatter -- Section I: Clays for Nanocomposites. Clays and Clay Minerals / Fa̐za Bergaya, Maguy Jaber, Jean-Fraṅois Lambert -- Organophilic Clay Minerals / Fa̐za Bergaya, Maguy Jaber, Jean-Fraṅois Lambert -- Industrial Treatments and Modification of Clay Minerals / Cinzia Della Porta -- Alkylammonium Chains on Layered Clay Mineral Surfaces / Hendrik Heinz -- Chemistry of Rubber₆Organoclay Nanocomposites / Luca Giannini, Attilio Citterio, Maurizio Galimberti, Dafne Cozzi -- Section II: Preparation and Characterization of Rubber₆Clay Nanocomposites. Processing Methods for the Preparation of Rubber₆Clay Nanocomposites / Yong-Lai Lu, Li-Qun Zhang -- Morphology of Rubber₆Clay Nanocomposites / Maurizio Galimberti, Valeria Rosaria Cipolletti, Simona Giudice -- Rheology of Rubber₆Clay Nanocomposites / Avraam I Isayev, Jaesun Choi -- Vulcanization Characteristics and Curing Kinetic of Rubber₆Organoclay Nanocomposites / Raquel Verdejo, Marianella Hernandez, Natacha Bitinis, Jose Mar̕a Kenny, Miguel Angel Lopez-Manchado -- Mechanical and Fracture Mechanics Properties of Rubber Compositions with Reinforcing Components / Katrin Reincke, Wolfgang Grellmann -- Permeability of Rubber Compositions Containing Clay / Brendan Rodgers, Weiqing Weng, John Soisson, Dave Lohse, Walter Waddell, Robert Webb -- Section III: Compounds with Rubber₆Clay Nanocomposites. Rubber₆Clay Nanocomposites based on Apolar Diene Rubber / Konstantinos G Gatos, J̤zsef Karger-Kocsis -- Rubber₆Clay Nanocomposites based on Nitrile Rubber / Konstantinos G Gatos, J̤zsef Karger-Kocsis -- Rubber₆Clay Nanocomposites Based on Butyl and Halobutyl Rubbers / C Philippe Magill, Dana K Adkinson, Ralf I Schenkel -- Rubber₆Clay Nanocomposites based on Olefinic Rubbers (EPM, EPDM) / Makoto Kato -- Rubber₆Clay Nanocomposites based on Thermoplastic Elastomers / Joseph H Koo, Ofodike A Ezekoye, Jason C Lee, Wai K Ho, Morgan C Bruns -- Section IV: Applications of Rubber₆Clay Nanocomposites. Automotive Applications of Rubber₆Clay Nanocomposites / Samar Bandyopadhyay, Sugata Chakraborty, Rabindra Mukhopadhyay -- Nonautomotive Applications of Rubber₆Clay Nanocomposites / Carrie A Feeney, Harris A Goldberg -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Nanocomposites (Materials); Rubber; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Nanocomposites (Materials); Rubber; Electronic books; Electronic books